One-pot synthesis of efficient multifunctional nitrogen-doped carbon dots with efficient yellow fluorescence emission for detection of hypochlorite and thiosulfate. Issue 43 (24th October 2022) - Gao, Yifang; Liu, Yang; Zhang, Huilin; Lu, Wenjing; Jiao, Yuan; Shuang, Shaomin; Dong, Chuan
Abstract : CD-based ratiometric fluorescence probes are of great significance for visual detection, but accomplishing this goal is still a particularly challenging task. Abstract : CD-based ratiometric fluorescence probes are of great significance for visual detection, but accomplishing this goal is still a particularly challenging task. Herein, nitrogen-doped carbon dots (NCDs) with bright yellow fluorescence were easily manufactured via a one-pot hydrothermal method for visual detection of hypochlorite (ClO − ) and thiosulfate (S2 O3 2− ) under UV light irradiation. The as-prepared NCDs demonstrate favorable water solubility, excellent biocompatibility, superior optical properties and low cytotoxicity. Strikingly, the fluorescence of the NCDs could be quenched with ClO − . Based on these results, an original fluorescent nanoprobe was constructed for the highly discriminating recognition of ClO − by oxidation of the amino groups on their surface to nitro groups. The assay covered the ranges from 0.067 to 19.33 μM and 24 to 98 μM with a limit of detection (S/N = 3) of as low as 0.013 μM. Remarkably, a growing peak appears at 537 nm and the emission at 492 nm shrinks with the introduction of S2 O3 2−, which demonstrates ratiometric fluorescence emission characteristics ( F 537nm / F 492nm ) in the range of 6.6–100 μM with a limit of detection (S/N = 3) of as low as 0.78 μM. In addition, the fluorescence color of the NCDs also changes (yellow-green-blue) after adding various ClO − concentrations. The fluorescence color of the NCDs–ClO − also changes (blue-green-yellow) after adding various S2 O3 2− concentrations. This excellent ratiometric fluorescence probe was successfully further used for nuclear imaging. Accordingly, an easy-to-prepare paper-based sensor to identify ClO − and S2 O3 2− was fabricated, which demonstrated their adaptability for in situ on-site testing. This research further opens up new opportunities for the development of efficient yellow fluorescent probes based on NCDs nanomaterials for visual detection, biomarking, and biomedical optical imaging.